KONTEKSTUALISASI HADIS-HADIS TENTANG PAKAIAN : STUDI PADA PAKAIAN TRADISIONAL MASYARAKAT MELAYU RIAU - Nurfauzy Lubis (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
Every societies lives a culture. No society grows without culture. Including the Prophet Muhammad who lived in Arab culture. Arab traditions have been embedded in their environment in various aspects of life, such as the culture of clothes. Arabic culture with Malayan culture is certainly different. So that to understand the hadith about clothing needs to use a cultural approach to understand the desired context of a hadith. This study aims to look at the hadith about how Prophet Muhammad dress and how contextualized with the traditional clothes of the Riau Malay community. Method of this research is library research. The results of this study indicate that although the traditional clothes of the Riau Malay people are not robes like the clothes that the Prophet used to wear, the spirit of Islamic doctrine in Riau Malay traditional clothes is reflected in the colors, motifs, and noble values contained in.